A fluorene-fused triphenodioxazine (FTPDO) based polymer with remarkable thermal stability and significantly enhanced charge transport performance in air. (September 2016) - Guo, Libing; Quinn, Jesse; Wang, Jianli; Guo, Chang; Li, Xu; Wang, Jinliang; Li, Yuning
Abstract: We report the synthesis of a novel electron acceptor building block, fluorene-fused triphenodioxazine (FTPDO ), and a donor-acceptor polymer based onFTPDO and bithiophene, PFTPDOBT . This new polymer possesses a narrow band gap (1.66 eV) with low-lying frontier energy levels and exhibits hole transport characteristics in organic thin film transistors (OTFTs). Thin films ofPFTPDOBT show remarkable thermal stability in air at temperatures of up to 250 °C with no noticeable differences in UV–Vis absorption characteristics in comparison to the films annealed in nitrogen. Surprisingly, OTFTs with the polymer thin films annealed in air and measured in air outperform significantly the devices annealed and measured in nitrogen. Highlights: A fluorene-fused triphenodioxazine (FTPDO ) and its copolymer are synthesized. The polymer has a narrow band gap and low-lying frontier energy levels. This polymer shows remarkable thermal stability and enhanced mobilities in air.